Politik Hukum Pengaturan Organisasi Sayap Partai Politik dalam Hukum Positif Indonesia - Putra Perdana Ahmad Saifulloh (Faculty of Sharia, Islamic State University (UIN) Prof. K.H. Saifuddin Zuhri Purwokerto, Indonesia, 2020)
This article aims to answers the problem of organizing the Political Parties Wings in Positive Law. This research used a normative juridical research method, with a statutory, historical, and conceptual approach. The result of this research shows that Legal Politics of the Wing of Political Parties in the Law on Political Parties in Indonesia is to strengthen political parties in carrying out broader articulation and aggregation of interests. As well as imparting significant role of political parties in carrying out their functions to connect with the people directly, especially in bridging and fighting for the people interests.